Pengembangan Subyek Baru dari Hukum Internasional - Supardan Mansyur; Zunnuraeni Zunnuraeni (Faculty of Law, University of Mataram, 2017)
Nowdays the status of subject of international law is one of the most controversies in international law, particularly in part of corporation (multinational entities) and non governmental organizations. Since the status of subject of international law gives entities rights and duties under international law, it is important to find out the new development in the subject of international law. The issue in this article is what is the new development on the establishment and recognition of subject of international law?. To solve the issue, this article using normative reseach with conceptual approach and historical approach. The conclusion withdrown is that The new development in the subject of international law is the debate on the establishment and recognition of corporations and Non Governmental Organization as subject of international law. The view that corporation and NGO should established as subject of international law is based on the important role those entities has played in international plane. However, regardless the important role they play, they can not considered as the subject of international law since the lack recognition from international community.